Antioxidant Activity Identification of Crude Extract of Halimeda sp. From the Seribu Islands Using Different Testing Methods (DPPH, CUPRAC, and FRAP) - Siti Balqis Huriyah; Sujaka Nugraha; Suci Lestari; Yohanes Harvinda (Study Program of Aquaculture, Department of Fisheries and Marine Science, Faculty of Agriculture, University of Mataram, 2026)
The green seaweed from the genus Halimeda is a marine biological resource that holds promise as a source of bioactive compounds, such as antioxidant compounds. The antioxidant activity may differ based on the assay technique since each technique relies on a unique reaction mechanism. This research intended to assess the antioxidant properties of crude Halimeda sp. extract from the Seribu Islands employing three techniques: DPPH, CUPRAC, and FRAP. The sample was obtained through maceration with methanol and subsequently assessed for free radical scavenging activity and metal ion reduction capability. The findings indicated that the CUPRAC method yielded the greatest antioxidant activity, scoring 147.91 µmol Trolox/g extract, while the FRAP method followed with 83.61 µmol Trolox/g extract. The DPPH method generated an IC₅₀ value of 226.09 mg/L. These varying values suggest that the chemical properties of the compounds in the extract react differently to each testing principle. Consequently, employing several antioxidant assays is essential for a more thorough assessment of the antioxidant capacity of Halimeda sp. seaweed extract.